Case Report: Identification of a novel LYN::LINC01900 transcript with promyelocytic phenotype and TP53 mutation in acute myeloid leukemia - Hu, Chengjun; Dai, Qiuxin; Zhang, Ruiyi; Yang, Huanping; Wang, Man; Gu, Kaili; Yang, Jiangang; Meng, Wenjun; Chen, Ping; Xu, Maozhong (Frontiers in Oncology, 2023)
Acute myeloid leukemia (AML) is a malignant disease of myeloid hematopoietic stem/progenitor cells characterized by the abnormal proliferation of primitive and naive random cells in the bone marrow and peripheral blood. Acute promyelocytic leukemia (APL) is a type (AML-M3) of AML. Most patients with APL have the characteristic chromosomal translocation t(15; 17)(q22; q12), forming PML::RARA fusion. The occurrence and progression of AML are often accompanied by the emergence of gene fusions such as PML::RARA, CBFβ::MYH11, and RUNX1::RUNX1T1, among others. Gene fusions are the main molecular biological abnormalities in acute leukemia, and all fusion genes act as crucial oncogenic factors in leukemia. Herein, we report the first case of LYN::LINC01900 fusion transcript in AML with a promyelocytic phenotype and TP53 mutation. Further studies should address whether new protein products may result from this fusion, as well as the biological function of these new products in disease occurrence and progression.